2008
DOI: 10.1164/rccm.200801-190oc
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Dysfunction in a Murine Model of Sleep Apnea

Abstract: CIH during sleep is associated with decreased libido in mice. The decreased expression of endothelial NOS protein in erectile tissue and the favorable response to tadalafil suggest that altered nitric oxide mechanisms underlie CIH-mediated ED. No changes in testosterone emerge after intermittent hypoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 60 publications
1
46
0
Order By: Relevance
“…A recent review by Hoyos and colleagues in this journal has summarized the available data on erectile dysfunction in the OSA patient population, and proposed that endothelial dysfunction, an early component of cardiovascular disease, may underlie the pathophysiologic link between OSA and erectile dysfunction [183]. Indeed, in a study from our laboratory in a murine model, we demonstrated that the reduced bioavailability of NO accounted for substantial components of the erectile dysfunciton reported in OSA [184].…”
Section: Erectile Dysfunctionmentioning
confidence: 70%
“…A recent review by Hoyos and colleagues in this journal has summarized the available data on erectile dysfunction in the OSA patient population, and proposed that endothelial dysfunction, an early component of cardiovascular disease, may underlie the pathophysiologic link between OSA and erectile dysfunction [183]. Indeed, in a study from our laboratory in a murine model, we demonstrated that the reduced bioavailability of NO accounted for substantial components of the erectile dysfunciton reported in OSA [184].…”
Section: Erectile Dysfunctionmentioning
confidence: 70%
“…In line with this, recent work using an animal model to determine the role of sleep apnea for ED, showed that sexual activity and spontaneous erections were reduced by chronic intermittent hypoxemia. At the same time, endothelial NO synthase expression was decreased, while testosterone levels remained unchanged [32]. Conversely, patients with altered bulbocavernosus reflex latency and signs of neuropathy showed higher AHI and spent more time at SaO 2 < 90%, suggesting a link between hypoxia and nerval dysfunction [33].…”
Section: Discussionmentioning
confidence: 97%
“…Reports about alterations in psychic, neural, hormonal, and/or vascular systems lead to the assumption of a multifactorial genesis [2,16,17]. Most likely, one or more of these parameters will be the key to the pathophysiology of OSA-induced OAB.…”
Section: Obstructive Sleep Apnea Syndromementioning
confidence: 99%